Electron correlations and pre-collision in the re-collision picture of high harmonic generation. (11th June 2018) - Mašín, Zdeněk; Harvey, Alex G; Spanner, Michael; Patchkovskii, Serguei; Ivanov, Misha; Smirnova, Olga
Abstract: We discuss the seminal three-step model and the re-collision picture in the context of high harmonic generation in molecules. In particular, we stress the importance of multi-electron correlation during the first and the third of the three steps of the process: (1) the strong-field ionization and (3) the recombination. We point out how an accurate account of multi-electron correlations during the third recombination step allows one to gauge the importance of pre-collision: the term coined by Eberly (17 private communication) to describe unusual pathways during the first, ionization, step.